Services and Resources to Engineers: A Case Study of Outreach and Marketing, Assessment, and Future Directions in a Research Library. - Matt Torrence (Issues in Science and Technology Librarianship)
The literature, activities, and resource needs of engineering students and faculty provide insight into a demographic that is often among the early-adopters of new technologies, tools, and methods of sharing information. Despite the often non-bibliographic nature of their research efforts, there are numerous elements of the traditional service model that remain relevant and integral to the engineering research patron base. New methods of in-person and virtual instruction, the improved promotion of research consultation, and data management are prime targets for efficient and effective service updates. This article outlines the current engineering research environment, using a large research institution as a model and case study for evaluation and future planning for outreach and service marketing. [ABSTRACT FROM AUTHOR]